2017
DOI: 10.1002/mbo3.534
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of chitosan against Burkholderia pseudomallei

Abstract: The ability of Burkholderia pseudomallei to persist and survive in the environment is a health problem worldwide. Therefore, the antibacterial activities of chitosan against four environmental isolates of B. pseudomallei from soil in Khon Kaen, Thailand, were investigated. Antibacterial activities were assessed by a plate count technique after treatment with 0.2, 0.5, 1, 2 or 5 mg ml−1 chitosan for 0, 24 and 48 hr. Chitosan at 5 mg ml−1 completely killed all four B. pseudomallei isolates within 24 hr, whilst 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…However, the antibacterial activity of chitosan isolated from locally available materials and commercial chitosan in this study was attained at very high concentrations of 3000 µg/ml and 4000 µg/ml. Kamjumphol et al 66 reported similar results where chitosan antibacterial activity was dose dependent and the most efficacious concentration was 5000 µg/ml. The low antibacterial activity may be attributed to fairly high molecular weight of chitosan.…”
Section: Discussionmentioning
confidence: 76%
“…However, the antibacterial activity of chitosan isolated from locally available materials and commercial chitosan in this study was attained at very high concentrations of 3000 µg/ml and 4000 µg/ml. Kamjumphol et al 66 reported similar results where chitosan antibacterial activity was dose dependent and the most efficacious concentration was 5000 µg/ml. The low antibacterial activity may be attributed to fairly high molecular weight of chitosan.…”
Section: Discussionmentioning
confidence: 76%
“…Each bacterial isolate from glycerol stock at -80°C was grown on Ashdown’s agar and incubated at 37°C for 48 h. A single colony of B . pseudomallei was inoculated into 3 mL of Luria-Bertani (LB) broth containing appropriate antibiotics and incubated at 37°C with shaking (200 rpm) for 18 h. A 2% inoculum was added into 25 mL fresh LB broth and further incubated until OD 540 = 0.8–0.9 to provide bacterial starter culture [ 27 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The functional groups of chitosan and chitosan oligosaccharide, such as hydroxylamines and acetylated amine groups, react with various cell receptors that initiate interconnected pathway reactions in the living cells. It is particularly responsible for its beneficial properties, such as anti-inflammatory (Leal et al 2010;Santos-Moriano et al 2018), anti-carcinogenic (Huang et al 2006), anti-diabetic (Ju et al 2010), antimicrobial (Kamjumphol et al 2018;Tanha et al 2017), anti-HIV-I (Vo and Kim 2010), antioxidant (Ngo et al 2009), and anti-angiogenic (Quan et al 2009) activities.…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%